2013
DOI: 10.1681/asn.2013020123
|View full text |Cite
|
Sign up to set email alerts
|

Nephrologist Caseload and Hemodialysis Patient Survival in an Urban Cohort

Abstract: Physician caseload may be a predictor of patient outcomes associated with various medical conditions and procedures, but the association between patient-physician ratio and mortality among patients undergoing hemodialysis has not been determined. We examined whether a higher patient-nephrologist ratio affects patient mortality risk using de-identified data from DaVita dialysis clinics and the U.S. Renal Data System. A total of 41 nephrologists with a caseload of 50-200 hemodialysis patients from an urban Calif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 37 publications
1
27
1
1
Order By: Relevance
“…This finding differs from findings of Harley et al [9], who studied prevalent patients undergoing dialysis in an urban Southern California area and reported higher mortality among those cared for by nephrologists with larger case loads. This difference likely reflects differences in patient populations and geographic distribution.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…This finding differs from findings of Harley et al [9], who studied prevalent patients undergoing dialysis in an urban Southern California area and reported higher mortality among those cared for by nephrologists with larger case loads. This difference likely reflects differences in patient populations and geographic distribution.…”
Section: Discussioncontrasting
confidence: 99%
“…This difference likely reflects differences in patient populations and geographic distribution. The Harley et al [9] study included only 41 nephrologists who practice in the greater Los Angeles area, and our study included all nephrologists who provided dialysis care to Medicare patients in the United States in 2006. The association between provider case load and patient outcomes might differ by geographic region.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Age, sex and socioeconomic circumstances also have an impact [47], as well as the number of patients under a physician's care [48]. …”
Section: Discussionmentioning
confidence: 99%
“…Ericksen et al, pointed out that rural dialysis patients have less nephrologist follow-up (18). Harley et al reported that a higher dialysis patient caseload in urban areas was associated with higher mortality, a relationship that may well hold for rural areas (19). Lichter and Parsi reported that "rural blacks are even more 'ghettoized' than blacks living in metro areas" (20).…”
Section: A Look Aheadmentioning
confidence: 99%